Design, modelling and simulation of controlled sepic DC-DC converter-based genetic algorithm - Mohammed Omar Ali; Ali Hussein Ahmad (Institute of Advanced Engineering and Science, 2020)
This paper discusses various aspects of a single-ended primary inductance DC-DC converter (SEPIC). The focus is on design, modelling, and simulation results of a SEPIC converter. The study analyses the principle of SEPIC operation when operated in continuous conduction mode (CCM). Additionally, the mathematical equations for the design modules are calculated as per converter requirements. State-space equations are used to formulate the state-space model of the SEPIC converter. To satisfy the best-performance criterion of the system, the parameters for controller (Kp, Ki, Kd) should be tuned or optimized using the genetic algorithm (GA) optimization technique. Controller parameters are determined using an objective function that minimises the integral time absolute error (ITAE). Simulations performed on a closed-loop system reveal that the step response with a PID controlled based GA displayed superior performance. A closed-loop system has a substantially bigger stability region compared to an open-loop system. The simulation optimised performance metrics like maximum overshoot percentage (Mp), rise time (tr), and settling time (ts). MATLAB/Simulink R2018a® and m-file code are used for the system modelling, simulation, and optimization of the PID controller parameters based on the GA.